2014
DOI: 10.1108/ijm-06-2013-0133
|View full text |Cite
|
Sign up to set email alerts
|

Workforce nationality composition and workplace flexibility in Britain

Abstract: Purpose-This paper, with an organisational focus, offers a novel examination of the association between workforce nationality composition and workplace flexibility practices (WFPs), an under-researched topic with high potential benefits at microeconomic and macroeconomic level. Design/methodology/approach-British data is used, as the United Kingdom (UK) has experienced significant immigrant flows and has a relatively high level of labour market flexibility. The Workplace Employee Relations Survey (WERS) 2011, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Regarding determinants of occupational mobility, this issue suggests that business cycle (Roosaar et al, 2014), numerical flexibility (Malk, 2014) and occupational categories (Neubecker, 2014;Roosaar et al, 2014) as well as sector (Roosaar et al, 2014) have an effect. Spatial mobility may have counterintuitive effects on individual occupational mobility depending on gender (Arbel et al, 2014;Masso et al, 2014) and explains various flexibilities at a firm level (Whyman and Petrescu, 2014). Finally, it is also demonstrated that different types of labour market flexibilities are inherently linked to each other (Ruiz, 2014;Whyman and Petrescu, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding determinants of occupational mobility, this issue suggests that business cycle (Roosaar et al, 2014), numerical flexibility (Malk, 2014) and occupational categories (Neubecker, 2014;Roosaar et al, 2014) as well as sector (Roosaar et al, 2014) have an effect. Spatial mobility may have counterintuitive effects on individual occupational mobility depending on gender (Arbel et al, 2014;Masso et al, 2014) and explains various flexibilities at a firm level (Whyman and Petrescu, 2014). Finally, it is also demonstrated that different types of labour market flexibilities are inherently linked to each other (Ruiz, 2014;Whyman and Petrescu, 2014).…”
mentioning
confidence: 99%
“…Spatial mobility may have counterintuitive effects on individual occupational mobility depending on gender (Arbel et al, 2014;Masso et al, 2014) and explains various flexibilities at a firm level (Whyman and Petrescu, 2014). Finally, it is also demonstrated that different types of labour market flexibilities are inherently linked to each other (Ruiz, 2014;Whyman and Petrescu, 2014).…”
mentioning
confidence: 99%